2015
DOI: 10.1074/jbc.m115.656181
|View full text |Cite
|
Sign up to set email alerts
|

Functional Architecture of the Cytoplasmic Entrance to the Cystic Fibrosis Transmembrane Conductance Regulator Chloride Channel Pore

Abstract: Background:The cytoplasmic entrance to the CFTR channel pore is not defined. Results: Functionally important positively charged amino acid side chains attract Cl Ϫ to the cytoplasmic entrance to the pore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 40 publications
(46 reference statements)
8
62
1
Order By: Relevance
“…The corresponding residues in zCFTR, K249, and K371, are both located at the cytoplasmic opening ( Figure 5). The same study also showed that positively charged residues along TM10 and TM12, the helices equivalent to TM4 and TM6 in the other half of CFTR, are not involved in comparable favorable electrostatic interactions with chloride ions (El Hiani and Linsdell, 2015). Entirely consistent with these functional studies, we did not observe a lateral portal (like that between TM4 and TM6) between TM10 and TM12 ( Figure S4).…”
Section: Asymmetric Nbd Associationsupporting
confidence: 86%
See 1 more Smart Citation
“…The corresponding residues in zCFTR, K249, and K371, are both located at the cytoplasmic opening ( Figure 5). The same study also showed that positively charged residues along TM10 and TM12, the helices equivalent to TM4 and TM6 in the other half of CFTR, are not involved in comparable favorable electrostatic interactions with chloride ions (El Hiani and Linsdell, 2015). Entirely consistent with these functional studies, we did not observe a lateral portal (like that between TM4 and TM6) between TM10 and TM12 ( Figure S4).…”
Section: Asymmetric Nbd Associationsupporting
confidence: 86%
“…The ion conduction pathway is connected to the cytosol through this opening. Studies of human CFTR have shown that R248 and K370 are important in recruiting chloride ions to the pore (El Hiani and Linsdell, 2015). The corresponding residues in zCFTR, K249, and K371, are both located at the cytoplasmic opening ( Figure 5).…”
Section: Asymmetric Nbd Associationmentioning
confidence: 99%
“…It is worth noting that this region is also found in a model of the open form of the CFTR channel ( Supplementary Figure 1A, RMSD 4.7 Å on 204 Cα, Mornon et al, 2015). This model, supported by experimental data (El Hiani and Linsdell, 2015) and consistent with the cryo-EM 3D structure at the level of individual blocks of TM helices (Hoffmann et al, 2018), gives insight into an alternative conformation of the CFTR channel, with a different configuration of the TM7-TM8 hairpin as well as of the N-terminal extension (lasso in the cryo-EM 3D structure), free for interaction with cytosolic partners (Supplementary Figure 1A).…”
Section: Position Of W361 On the Cftr 3d Structures And Possible Invosupporting
confidence: 77%
“…Based on atomic homology modeling and molecular dynamics studies, it was proposed that such access may be provided not by a central pathway, but instead by one or more (possibly up to four) lateral entrances between individual transmembrane domain cytoplasmic extensions (TMEs) [27,28]. The first functional evidence for the existence of such cytoplasmic lateral portals to the pore came from substituted cysteine accessibility mutagenesis work that identified porelining, positively charged amino acid side chains within the TMEs and apparently surrounding two potential portals [29]. Subsequent, more detailed biophysical analysis suggested that there is only one functional portal involved in the entry of cytoplasmic Cl − ions into the pore, and indicated that four positively charged residues -K190 (TME3), R248 (TME4), R303 (TME5) and K370 (TME6)play major roles in attracting cytoplasmic Cl − ions to the pore via this portal [30].…”
Section: The Structure Of Cftr Suggests Conformational Transitions Tymentioning
confidence: 99%
“…This portal is facing the viewer in (b), and on the right hand side of the MSDs in (c), indicating cytoplasmic access as indicated by the arrows. (d) A cross-section through the TMEs indicates the location of the portal (arrow), as well as important positively charged amino acid side chains (red; K190 (TME3), R248 (TME4), R303 (TME5) and K370 (TME6) in human CFTR) that have been shown to play functional roles in the electrostatic attraction of cytoplasmic anions to the pore[29,30].…”
mentioning
confidence: 99%